1988
DOI: 10.1002/cne.902730109
|View full text |Cite
|
Sign up to set email alerts
|

Regional and laminar distribution of the dopamine and serotonin innervation in the macaque cerebral cortex: A radioautographic study

Abstract: The regional density and laminar distribution of dopamine (DA) and serotonin (5-HT) afferents were investigated in the cerebral cortex of cynomolgus monkeys using a radioautographic technique that is based on the high affinity uptake capacity of these aminergic neurons. Large vibratome sections, 50 micron thick, were incubated with [3H] DA (0.2 microM) and desipramine (5 microM) or with unlabeled norepinephrine (5 microM) and [3H] 5-HT (0.6 microM), which allowed for the specific labeling of the DA and 5-HT in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
133
3

Year Published

1996
1996
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 248 publications
(144 citation statements)
references
References 71 publications
8
133
3
Order By: Relevance
“…This observation was previously made in humans, with the suggestion that this pattern could have evolutionary implications (Gaspar et al, 1989). This pattern of sublaminar innervation in the molecular layer has been reported in agranular cortices of long-tailed macaque monkeys (Berger et al, 1988), but may have been extended in humans to include both agranular and granular cortices (Gaspar et al, 1989). …”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…This observation was previously made in humans, with the suggestion that this pattern could have evolutionary implications (Gaspar et al, 1989). This pattern of sublaminar innervation in the molecular layer has been reported in agranular cortices of long-tailed macaque monkeys (Berger et al, 1988), but may have been extended in humans to include both agranular and granular cortices (Gaspar et al, 1989). …”
Section: Discussionsupporting
confidence: 69%
“…A detailed analysis that included long-tailed macaques (Macaca fascicularis) and squirrel monkeys (Saimiri sciureus) did not report the presence of TH-ir coils within the cortical mantle (Lewis et al, 1987). Another study of Macaca fascicularis reported "clusters" of DAergic fibers in the upper portion of layer III of the motor areas 4 and 6, but not in other cortical areas (Berger et al, 1988). Similarly, we did not find any coil-like TH-stained structures in the frontal cortex of any species of Old World monkeys that we examined, whereas coils were consistently present in great apes.…”
Section: Discussionmentioning
confidence: 99%
“…This signal was found in PMd in the present study (Figs. 3,4 and 6), and its properties supported the possibility that it reflects inputs from dopaminergic cells, perhaps those projecting directly to PMd (Lewis et al, 1987;Berger et al, 1988;Gaspar et al, 1992;Williams and Goldman-Rakic, 1993). If so, then blockade of dopamine receptors at the cortical level should eliminate this signal.…”
Section: Error and Reward-prediction Signals In Population Activitymentioning
confidence: 97%
“…However, reasonable candidates include dopaminergic (DA) neurons in the ventral tegemental area (VTA) and the substantia nigra pars compacta (SNc) that might influence activity in visual cortex via direct projections to early areas of visual cortex (Berger et al 1988(Berger et al , 1991Devoto and Flore 2006). However, these projections are generally thought to be sparse, so it is likely that indirect DA signals relayed through the striatum and then to frontal and parietal cortex play an important role in regulating value-related changes in early visual cortex (Barraclough et al 2004;Ding and Hikosaka 2006;Dorris and Glimcher 2004;GlĂ€scher et al 2009;Glimcher 2003;Hikosaka et al 2008;Hollerman and Schultz 1998;Ikeda and Hikosaka 2003;Lau and Glimcher 2007;Leon and Shadlen 1999;Luk and Wallis 2009;Platt and Glimcher 1999;Schultz and Dickinson 2000;Seo et al 2007;Sugrue et al 2004;Wallis and Miller 2003;Watanabe 1996).…”
Section: Value and Population Responses In Human Visual Cortexmentioning
confidence: 99%